Impact of abundance weighting on the response of seed traits to climate and land use - Pakeman, Robin J; Garnier, Eric; Lavorel, Sandra; Ansquer, Pauline; Castro, Helena; Cruz, Pablo; Doležal, Jiri; Eriksson, Ove; Freitas, Helena; Golodets, Carly; Kigel, Jaime; Kleyer, Michael; et al. (The Journal of ecology, 2008)
1. Many studies have identified relationships between plant reproductive behaviour and environmental conditions. However, they have all been based on cross-species analysis and take no account of the relative abundance of species with vegetation. 2. Using two reproductive traits - seed mass and dispersal vector - as examples, a range of previously identified relationships were tested using both unweighted and weighted-by-abundance data collected from land-use transitions at 12 sites across Europe. 3. Seed mass was correlated positively with most measures of temperature (stronger relationships for unweighted data) and declined against measures of disturbance (stronger relationships with weighted data). It was not related consistently to measures of water availability. 4. There was some evidence that endozoochory was associated with damper environments, hoarding with drier ones and exozoochory with more fertile habitats. 5. Weighting reduced the slope of relationships between seed mass and environmental variables, possibly indicating that dominance within vegetation is determined by land use after the operation of a climatic filter. Fewer significant relationships were detected for weighted dispersal mechanisms compared to unweighted ones, indicating less difference of the dominants from other species with regard to this trait. 6. Synthesis. This analysis shows that weighting by abundance in the vegetation (compared to unweighted analysis) has a significant impact on the relationships between key species traits and a range of environmental parameters related to climate and land use, and that this impact was not consistent in its effects.